Phraseological Image of Wealth and Poverty in Slovenian and Ukrainian Languages - Nikolovski, Gjoko; Kokolska, Vitalina (Slavistična prepletanja 6, 2025)
The article presents the phraseological image of wealth and poverty, which is revealed through Slovenian and Ukrainian phraseological units. On the basis of semantic analysis, the collected phraseological material is classified into groups representing wealth as a phenomenon that has its origin, a large amount of money, living in prosperity, extravagance and improvement of material position. The phenomenon of poverty is linked to lack of money, food, homelessness and begging, survival, debt and deterioration in material condition. The initial hypothesis of the paper is that the phraseological view of wealth and poverty in Slovenian and Ukrainian is consistent with the sociological definition of both phenomena.